Association of Dyslipidemia with Uterine Fibroid: A Case Control Study - Afruza, Shahzadi; Hossain, AKM Azad; Jahan, Jesmin; Sharmin, Asma; Naznin, Halima; Md Shameem, - (TAJ: Journal of Teachers Association, 2020)
Background & objective: Uterine fibroid (UF) is the most common gynaecological neoplasm. Despite the major public health impact of UF, little is known about their association. Some studies focused on the similarities between the common biological mechanisms underlying the development of UF and atherosclerotic plaques. So, it is possible to hypothesize that same atherogenic risk factors, such as dyslipidemia may play a role in UF pathogenesis. This study was carried out to investigate the lipid profile in patients with UF and to analyze the association of dyslipidemia with UF. Materials & Methods: This case-control study was carried out in the outpatient and inpatient Department of Obstetrics & Gynaecology, BSMMU, Shahbag, Dhaka over a period of 12 months between March 2017 to February 2018. Participants were 100 in number and aged between 18 and 45 years. Cases consisted of 50 women with uterine fibroids diagnosed by ultrasonography attending the outpatient and inpatient department of obstetrics and gynaecology, BSMMU, having no previous hormonal treatment. A similar number of age matched women without UF visiting the same gynaecological outpatient clinic for routine reasons were recruited as controls. Women who were postmenopausal, pregnant, diagnosed cases of malignant diseases, diagnosed cases of hypertension, diabetes mellitus, thyroid disease, CLD and CKD and women undergoing hormonal therapy were excluded from the study. Fasting lipid profiles were determined in blood samples taken from each participant. Atherogenic index was also calculated. Chi-square test was used for testing statistical significance. Statistical significance was set at p < 0⋅05. Results: Women with UF were found to have significantly higher levels of serum TC, TG and significantly lower level of HDL-C compared to the controls (p<0.05). The mean atherogenic index was 4.30±1.41 in case group and 2.86±0.97 in control group. The difference was statistically significant (p<0.05) between two groups. Conclusion: There is an association between dyslipidemia and UF. Women with UF have higher atherogenic index compared to women without UF. TAJ 2020; 33(2): 100-106